MULTIMEDIA AND CONVERGENCE AS FACTORS OF THE DEVELOPMENT OF REGIONAL INTERNET MEDIA (ON THE EXAMPLE OF THE MASS MEDIA OF THE REPUBLIC OF TATARSTAN) - A. Nagovitsyna, Tatiana; R. Gazizov, Ramis (Gênero & Direito, 2019)
The authors focus on such properties of regional Internet media as multimedia and convergence, which fully meet the requirements of the modern media market. Covering this topic, the authors focus on Internet publications of the Republic of Tatarstan. The specifics of the Internet media significantly changed the work of the journalists themselves, the nature of the submission of materials, the target audience, and the whole system of functioning of the media in general. The authors state that in recent years there has been a significant change in the media system due to the emergence and development of the Internet media, which not only took its place in it, but also determined the leading trends in its functioning. It is also important to study the influence of special features of network journalism on the media system in terms of their historical development and the mutual influence of Internet journalism and the technologies of the global network. The increasingly active use of multimedia technologies in the media and the very transformation of the multimedia character continue to change the format of journalistic activity. It is relevant to consider the influence of multimedia on the nature of structural and content changes that determine the forms of information delivery in regional media. The experience of the Internet media of the Republic of Tatarstan is generalized, which have broad opportunities to influence public opinion.